BUKU CERITA GAMBAR SEBAGAI MEDIA PENINGKATAN MINAT BACA SISWA SEKOLAH DASAR - Friska Ria Sitorus; Febri Ramadanu; Hanna Simanjuntak; Nurdiana - (Jurnal Bahasa Indonesia Prima (JBIP), 2023)
The reading ability of Elementary students is a series of actions that must be developed so that students are not only good at reading but also able to explore and understand the text of reading books. This study shows that several picture books are an effort to increase elementary school students' reading interest. The methodology used in this study is a literature review and reports from various journals. To increase students' interest in reading, teachers must use appropriate media to attract students' attention. Picture storybooks have a function to enrich and support storytelling in the process of understanding the contents of the book. Picture books are one of the tools used in the curriculum. Storybooks feature many pictures to tell a story, character, setting, or whatever. This study describes the development of Elementary school picture storybooks and the benefits of using storybooks as a media in teaching elementary students. The study concludes that students' attraction to develop reading skills and develop previous skills can be done through the use of media, namely the use of stories presented in the media.